Arithmetic
Additive Identity
Associative Property
Averages
Brackets
Closure Property
Commutative Property
Conversion of Measurement Units
Cube Root
Decimal
Distributivity of Multiplication over Addition
Divisibility Principles
Equality
Exponents
Factors
Fractions
Fundamental Operations
H.C.F / G.C.D
Integers
L.C.M
Multiples
Multiplicative Identity
Multiplicative Inverse
Numbers
Percentages
Profit and Loss
Ratio and Proportion
Simple Interest
Square Root
Unitary Method
Algebra
Algebraic Equation
Algebraic Expression
Cartesian System
Linear Equations
Order Relation
Polynomials
Probability
Standard Identities & their applications
Transpose
Geometry
Basic Geometrical Terms
Circle
Curves
Angles
Define Line, Line Segment and Rays
Non-Collinear Points
Parallelogram
Rectangle
Rhombus
Square
Three dimensional object
Trapezium
Triangle
Quadrilateral
Trigonometry
Trigonometry Ratios
Data-Handling
Arithmetic Mean
Frequency Distribution Table
Graphs
Median
Mode
Range
Home >> Polynomials >> Find Value of Polynomial >>

Find Value of Polynomial

Ordering of Polynomials Types of Polynomials Addition of Polynomials Subtraction of Polynomials Multiplication of Polynomials
Division of Polynomials Types of Degree / Powers in Polynomials Difference between Polynomials of Integers & Rationals Factoring of Quadratic Polynomials Find Value of Polynomial
Find Zero of Polynomial Remainder Theorem in Polynomial

Value of a polynomial is obtained when variables of given polynomial are interchanged or replaced by the value of variable.

Letís study the following examples to understand with the help of below examples:

Example 1: Find the value of following polynomial where x = 2
p(x) = x2 + 4x + 4

Solution: Given polynomial:
p(x) = x2 + 4x + 4

Value of given polynomial when x = 2 and we get:
p(2) = (2)2 + 4 (2) + 4

Solve exponential forms and we get:
= 4 + 8 + 4

Solve the addition expression and we get:
= 16

Hence the value of p(x) = x2 + 4x + 4, where x = 2, is 16



Example 2: Find the value of following polynomial where y = 1
p(y) = 2y3 + y2 + 3

Solution: Given polynomial:
p(y) = 2y3 + y2 + 3

Value of given polynomial when y = 1 and we get:
p(1) = 2 (1)2 + (1)2 + 3

Solve exponential forms and we get:
= 2 + 1 + 3

Solve the addition expression and we get:
= 6

Hence the value of p(y) = 2y3 + y2 + 3, where y = 1, is 16



Example 3: Find the value of following polynomial where a = -2
p(a) = a3 + a2 - 10

Solution: Given polynomial:
p(a) = a3 + a2 - 10

Value of given polynomial when a = -2 and we get:
p(-2) = (-2)3 + (-2)2 - 10

Solve exponential forms and we get:
= (-8) + 4 - 10

Solve the above expression and we get:
= (-18) + 4
= (-14)

Hence the value of p(a) = a3 + a2 - 10, where a = -2, is (-14)


Follow us on :

Terms & Conditions

All rights reserved